Studi Tentang Faktor Terkait Minat Beli Konsumen KFC di Batam - Mistianasari, Dita; Ngaliman, Ngaliman; Yanti, Sri (Zona Manajerial: Program Studi Manajemen (S1), 2023)
Competition in the fast food business in Batam has been quite high in the last five years. Each restaurant serves a variety of attractive menus and packages. As a fast food restaurant business that is well known to the public, KFC must carry out an analysis to find out the perceptions that are built in customers' minds. For example, price, service quality and promotions have an impact on consumer buying interest. The aim of this research is to determine the respective influences of price perception, service quality and promotion on consumer buying interest at KFC Batam. The research method used is a survey. Against 10 KFC branches in Batam, 100 respondents were determined. The results of this research show that price perception, service quality and promotion partially influence KFC buying interest in Batam City.